Penyuluhan Tentang Cara Mencuci Tangan Dengan Baik Dan Benar Menggunakan Sabun di TK ABA - Ali Apriansyah; Nadya Salsabilla; Ayu Nalaratih; Fidiyanti Amatilah; Rena Prizka Melia; Tian Septian Nugraha (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2021)
Background : Counseling on how to wash hands properly and correctly using soap is one of the Clean and Healthy Life Behaviors (PHBS). Childhood is a period full of physical activity. The number of activities carried out by children makes children also deal with dirt, sweat and of course germs. To minimize germs in these children's bodies, it is necessary to teach them how to wash their hands properly. Children in ABA Kindergarten do not yet know and do not understand how to wash their hands properly. This is the reason that drives us to promote proper hand washing in ABA Kindergarten. Objective: To increase the knowledge of ABA Kindergarten children about how to wash their hands properly and correctly using soap and water. Methods: This research was conducted by means of lectures followed by demonstrations as well as the practice of washing hands and playing games using a spinner. Results: Providing counseling on how to wash hands in orphanages can increase knowledge and skills in dealing with clean and healthy living. Conclusion: There is an effect of providing counseling about PHBS to ABA Kindergarten children.